Pengaruh Model Komunikasi dalam Meningkatkan Pengetahuan dan Sikap Remaja Terhadap Deteksi Dini Penyakit Tuberkulosis - Uswatun Khasanah; Rusnita Rusnita; Idhar Darlis (Universitas Malahayati, 2026)
ABSTRACT Tuberculosis (TB) remains a public health problem; early detection among adolescents requires a communication approach tailored to the school context. This study aimed to assess the effect of a participatory communication model on adolescents’ knowledge and attitudes regarding early TB detection. A quantitative quasi-experimental study with a pretest–posttest control group design was conducted at SMAN 21 Makassar. The population comprised all 11th-grade students; a sample of 206 was calculated using Slovin’s formula (5%) and evenly allocated to an intervention group (n=103) and a control group (n=103) by class to minimize contamination. Measurements employed standardized questionnaires before and after the intervention. Assumption tests included Shapiro–Wilk and Levene; within-group analyses used paired t-tests or Wilcoxon signed-rank tests according to distribution. Results showed that, in the intervention group, mean knowledge increased from 13.21±2.10 to 16.44±1.95 (Δ=3.23±1.55; p0.001), whereas in the control group it rose from 13.08±2.05 to 13.87±2.18 (Δ=0.79±2.19; p=0.059). The proportion with “adequate” knowledge increased from 49.5% to 84.5% in the intervention group but decreased from 44.6% to 40.8% in the control group. Mean attitude scores in the intervention group increased from 11.93±2.00 to 15.67±1.98 (Δ=3.74±1.67; p0.001), while the control group showed a smaller increase from 12.04±2.05 to 13.00±2.00 (Δ=0.96±1.95; p=0.080). Conclusion: the participatory communication model effectively improves adolescents’ knowledge and fosters positive attitudes toward early TB detection, and is therefore suitable for integration into school-based health promotion programs. Keywords: Communication Model, Knowledge, Adolescents, Attitudes, Tuberculosis. ABSTRAK Tuberkulosis (TBC) tetap menjadi masalah kesehatan publik; deteksi dini pada remaja memerlukan pendekatan komunikasi yang sesuai konteks sekolah. Penelitian ini bertujuan menilai pengaruh model komunikasi partisipatif terhadap pengetahuan dan sikap remaja terkait deteksi dini TBC. Studi kuantitatif quasi-eksperimental dengan pretest–posttest control group dilaksanakan di SMAN 21 Makassar. Populasi adalah seluruh siswa kelas XI; besar sampel 206 orang dihitung dengan Slovin (5%) dan dialokasikan seimbang ke kelompok intervensi (n=103) dan kontrol (n=103) berbasis kelas untuk meminimalkan kontaminasi. Pengukuran menggunakan kuesioner terstandar sebelum dan sesudah intervensi. Uji asumsi meliputi Shapiro–Wilk dan Levene; analisis dalam-kelompok menggunakan paired t atau Wilcoxon sesuai distribusi. Hasil menunjukkan pada kelompok intervensi rerata pengetahuan meningkat dari 13,21±2,10 menjadi 16,44±1,95 (Δ=3,23±1,55; p0,001), sedangkan kontrol 13,08±2,05 menjadi 13,87±2,18 (Δ=0,79±2,19; p=0,059). Proporsi pengetahuan “cukup” naik dari 49,5% menjadi 84,5% pada intervensi dan turun dari 44,6% menjadi 40,8% pada kontrol. Rerata sikap pada intervensi naik dari 11,93±2,00 menjadi 15,67±1,98 (Δ=3,74±1,67; p0,001), sedangkan kontrol meningkat kecil dari 12,04±2,05 menjadi 13,00±2,00 (Δ=0,96±1,95; p=0,080). Simpulan: model komunikasi partisipatif efektif meningkatkan pengetahuan dan membentuk sikap positif remaja terhadap deteksi dini TBC, sehingga layak diintegrasikan dalam program promosi kesehatan berbasis sekolah. Kata Kunci: Model Komunikasi, Pengetahuan, Remaja, Sikap, Tuberkulosis.